Soil-Specific Efficacy of Mechanised Rice Planting and Weeding Equipment: A Multi-Terrain Evaluation - Kannan, S. Vallal; Sangeetha Jebalin, V. V. (Current Research Progress in Agricultural Sciences Vol. 5, 2024)
Labour availability is one of the factors deciding the timely completion of sowing or transplanting at peak seasons of delta areas in rice cultivation. Mechanisation supports the timely completion of operations and supports maintaining productivity with less cost of cultivation. Machinery performance especially depends on the soil type and crop ecosystem. With this background, the experiment was conducted with the objectives to assess the performance of current rice transplanter models and power weeder models, in different soil conditions and reduce cultivation costs while improving rice production and profitability. A strip plot design was used, with major three soil types as the main plot treatments, existing rice transplanter five models as the sub-plot treatments, and current power weeder three models as the sub-sub-plot treatments. Among the growth and yield parameters, the 6-row walking type transplanter combined with a cono weeder showed superior performance, recording higher tillers and productive tillers (16.28 and 20.65 per hill), filled grains (113 and 145 per panicle), and seed yields (5922 and 5733 kg ha-1) in sandy clay loam and sandy loam soils, respectively. This combination also achieved higher net returns (Rs. 70,195 ha-1 and Rs. 55,343 ha-1) and benefit-cost ratios (BCRs) of 2.62 and 2.28. Additionally, it resulted in an extra grain yield of 1769 kg ha-1 and 1873 kg ha-1, with an additional net profit of Rs. 37,027 ha-1 and Rs. 34,813 ha-1 for sandy clay loam and sandy loam soils, respectively. In clay loam soil, the riding type 8-row transplanter combined with a single-row power weeder produced higher productive tillers (15.25 per hill), filled grains (122 per panicle), and seed yields (5506 kg ha-1), along with a higher net return of Rs. 58,175 ha-1 and a BCR of 2.32. This combination also resulted in an additional grain yield of 1121 kg.ha-1, leading to an extra net profit of Rs. 24,618 ha-1 and a corresponding net income increase compared to traditional farming practices. In conclusion, using the 6-row riding type transplanter and cono weeder, along with appropriate agronomic practices, is the key to achieving higher yields, net returns, and BCR in sandy clay loam and sandy loam soils. Similarly, the 8-row riding transplanter combined with a single-row power weeder is essential for higher yield performance and profitability in clay loam soil.